Lack of Serum Creatinine Decrease After Coronary Angiography Despite Prophylactic Hydration After Routine Coronary Angiography/Angioplasty in Stable Angina Patients - Pilot Study - Pawel Burchardt; Janusz Rzezniczak; Tomasz Synowiec; Dariusz Angerer; Anna Palasz; Jakub Zurawski (Karger Publishers, 2016)
Background/Aims: To prevent contrast induced renal dysfunction a periprocedural prophylactic hydration is applied. Due to dilution it should cause a drop in serum creatinine concentration (SCR). Surprisingly, no reduction in SCR after contrast admission is found in up to 25% of patients as early as 12-18 hours after coronary angiography/angioplasty. This study aims to find a clinical explanation as well as predict circumstances for this phenomenon. Methods: Retrospective clinical and laboratory data was used from 341 patients who underwent elective coronary angiography/angioplasty, received a prophylactic hydration, and had serum creatinine concentration measured prior to, and 12-18 hours after invasive procedure with iodine contrast administration. To exclude an improper hydration due to no creatinine decrease, the number of red blood cells was analysed as well as hemoglobin and hematocrit in blood donations collected during the study time points. Results: The resulting lack of serum creatinine reduction could be explained by dehydration (measured by increase in number of RBC, HGB and HCT) only in 13.5% , 10.8 %, and 20% of cases, respectively. Any form of abnormal glucose metabolism combined with either baseline serum creatinine concentration 86.77 mL/min, or GFR by CKD EPI >80.08 mL/min/1.73 m2, or GFR by MDRD >74.48 mL/min/1.73 m2 were the predictors for no creatinine decrease at outcome. Additionally, it was demonstrated that the lack of creatinine decrease was more often observed among those patients whose initial renal function was better than in the subjects with reduction of SCR. Conclusions: This observation requires further prospective investigation on extended group of patients.